Adoption of Agro-forestry Patterns and Crop Systems Around Register 19 Forest Park, Lampung Province, Indonesia - Christine Wulandari; Pitojo Budiono; Slamet Budi Yuwono; Susni Herwanti (Jurnal Manajemen Hutan Tropika, 2014)
To return the ecological function of Wan Abdul Rachman Forest Park, it must be involved the role of buffer zone communities living around the forest by optimizing the cultivated land with applying agro-forestry based on socio-economic conditions in the community, such as community preferences and adoption of agro-forestry patterns. Under these conditions it is necessary to hold a study concerning to the level of community preference to the type of plants and the level of adoption, as well as the NPV analysis of the 3 patterns of agro-forestry which are applied by the majority of community around the forest park. Results of the study revealed that there were 3 dominant plant types  preferred by the community in the forest park, namely: coffee (30.8%), cacao (35.8%), and rubber (17.4%). Based on these crops, there were 3 agro-forestry patterns practiced by the majority of community in their cultivated land. They were: (1) coffee-cacao-wooden plants, and fruits (47%), (2) rubber-coffee-wooden plants, and fruit (35%), and (3) rubber-cacao-wooden plants, and fruit (18%). The highest personal and social NPVs obtained  in the agro-forestry pattern of rubber-coffee-wooded plants, and fruits were IDR4.589.627.36 and IDR6.454.806.01, respectively. To ensure the sustainability of the program, the development of communities living around the forest together with a program of community empowerment in the block of utilization and social forestry in the forest park are recommended to continue, based on the Regional Regulation (PerDa) Number. 3/2012.